2002
DOI: 10.1016/s1074-7613(02)00482-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Modification for Rapid Display of Proteins as a Novel Means of Immunomodulation

Abstract: Long-term display of exogenous proteins on the cell surface may have important research and therapeutic implications. We report a novel method for the cell-surface display of proteins that involves generation of a chimeric protein with core streptavidin, biotinylation of cells, and "decoration" with the protein. A chimeric protein with the extracellular portions of FasL (SA-FasL) was efficiently displayed on the cell surface within 2 hr without detectable cellular toxicity. Biotin and SA-FasL persisted on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
169
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 88 publications
(176 citation statements)
references
References 38 publications
7
169
0
Order By: Relevance
“…Activated cells were then preincubated with a high concentration (4 g/ml) of SA-4-1BBL for 45 min on ice, washed extensively, and used for suppression assay. To differentiate between the proliferation of CD4 ϩ CD25 ϩ and CD4 ϩ CD25 Ϫ T cells in coculture experiments, CD4 ϩ CD25 Ϫ or CD4 ϩ CD25 ϩ T cells were labeled with CFSE (Molecular Probes) (43) and used in suppression assays as described. Proliferation was assessed using flow cytometry.…”
Section: Suppression Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated cells were then preincubated with a high concentration (4 g/ml) of SA-4-1BBL for 45 min on ice, washed extensively, and used for suppression assay. To differentiate between the proliferation of CD4 ϩ CD25 ϩ and CD4 ϩ CD25 Ϫ T cells in coculture experiments, CD4 ϩ CD25 Ϫ or CD4 ϩ CD25 ϩ T cells were labeled with CFSE (Molecular Probes) (43) and used in suppression assays as described. Proliferation was assessed using flow cytometry.…”
Section: Suppression Assaysmentioning
confidence: 99%
“…injection. Donor islets were harvested from fully mismatched C57BL/6 mice and transplantation was performed as previously described (43). Transplanted animals were monitored three times weekly and rejection confirmed by two consecutive blood glucose readings over 300 mg/dl.…”
Section: Islet Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…16,43,49 Presentation of auto or transplantation antigens in conjunction with FasL leads to the activation of T cells and expression of Fas. Subsequent engagement of Fas with FasL on antigen-presenting cells (APCs) results in apoptosis of T cells ( Figure 3A-B).…”
Section: Systemic Immunomodulation With Faslmentioning
confidence: 99%
“…61 In contrast, Yolcu et al reported extended survival of allogeneic islets cotransplanted with allogeneic biotinylated splenocytes "decorated" with a metalloproteinase cleavage site-deficient FasL molecule chimeric with streptavidin (SA-FasL). 43 The main For personal use only. on May 10, 2018. by guest www.bloodjournal.org From functional differences between these modified molecules appeared to be their chemotactic effect on neutrophils.…”
mentioning
confidence: 99%